Roma writings : Romani literature and poetry in Central, South-eastern and Eastern Europe from the 19th century to World War II - Roman, Raluca Bianca; Roman, Raluca Bianca; Zakhova, Sofii͡a; Zakhova, Sofii͡a; Marinov, Aleksandar G.; Marinov, Aleksandar G. (Brill / Ferdinand Schöningh, 2021)
The book focuses on the early period of Roma publishing (from the nineteenth century until the Second World War) when the first original texts, fiction and media publications authored by Roma appeared. Based on extensive archival and historical research, including the discovery of earlier, up to now unknown sources, the literary activities of Roma in Central, South-eastern and Eastern Europe are discussed in their historical context and interrelation with the birth of the Roma emancipatory movement. Romani literature and press are thus embedded in the history and literary studies of the European national literatures.